The study on role of endothelial cell autophagy in rats with sepsis-induced acute kidney injury - Ran Pang; Lei Dong; Jingfeng Liu; Xiaojun Ji; Haizhou Zhuang; Meili Duan (Heliyon, 2023)
Sepsis often causes acute kidney injury (AKI). Autophagy of renal tubular epithelial cells is considered a cytoprotective mechanism in septic AKI; however, the role of autophagy of renal endothelial cells is uninvestigated. The current study examined whether autophagy was induced by sepsis in renal endothelial cells and whether induction of autophagy in these cells attenuated the degree of AKI. Cecal ligation and puncture (CLP) was used as a model of sepsis in rats. Four experimental groups included: sham, CLP alone, CLP + rapamycin (RAPA), and CLP + dimethyl sulfoxide (DMSO), where RAPA was used as an activator of autophagy. CLP increased renal LC3-II protein levels with an additional transient increase by RAPA at 18 h. In addition, CLP induced autophagosome formation in renal endothelial cells had an additional increase induced by RAPA. Interestingly, the levels of bone morphogenetic protein and activin membrane-bound inhibitor (BAMBI), an endothelial cell-specific protein in the kidney, were also increased by CLP, albeit it was transiently downregulated by RAPA at 18 h. Serum thrombomodulin increased and renal vascular endothelial (VE)-cadherin decreased following CLP, and these changes were attenuated by RAPA. The renal cortex exhibited and inflammatory tissue damage after CLP, and RAPA alleviated these histopathological injuries. The current findings indicate that autophagy was induced by sepsis in renal endothelial cells, and upregulation of autophagy in these cells alleviated endothelial injury and AKI. In addition, BAMBI was induced by sepsis in the kidney, which may play a role in regulating endothelial stability in septic AKI.